Transcriptome Analyses Reveal IL6/Stat3 Signaling Involvement in Radial Glia Proliferation After Stab Wound Injury in the Adult Zebrafish Optic Tectum - Shimizu, Yuki; Kiyooka, Mariko; Ohshima, Toshio (Frontiers in Cell and Developmental Biology, 2021)
Adult zebrafish have many neurogenic niches and high regenerative capacity in central nervous system compared to mammals including human and rodents. In the zebrafish optic tectum, most of radial glia are quiescent in the physiological condition while stab wound injury induces RG proliferation and differentiation into newborn neurons. Although functional analyses of molecular mechanisms and transcriptomic analyses for RG proliferation and differentiation have been investigated, cellular response and global gene expression changes focusing on the early stages of tectum regeneration have not well understood. In present study, histological analyses showed increase in Isolectin B4+ macrophages prior to the induction of RG proliferation. Moreover, transcriptome and pathway analyses based on upregulated differentially expressed genes identified enriched pathways; apoptosis, innate immune system, cell proliferation, cytokine signaling, p53 signaling and IL6/Jak-Stat signaling. Among them, we found that Stat3 inhibition suppressed RG proliferation after the stab wound injury and that IL6 administration into cerebroventricular fluid activates RG proliferation without injury. These transcriptomic and functional analyses reveal IL6/Stat3 signaling is one of initial triggers for RG activation during optic tectum regeneration.